The importance of doctor-patient and nurse-patient communication in clinical nursing practice (医患沟通在临床护理中的重要性探讨) - HU Fang (胡芳) (中西医结合护理)
Harmonious doctor-patient and nurse-patient communication are prerequisite for establishing a strong relationship with patients and ensuring the quality of nursing. This paper introduced the basic concept of doctor-patient communication, analyzed the role of doctor-patient and nurse-patient communication in clinical nursing work, investigated effective strategies of doctor-patient and nurse-patient communication, and provided reference for clinical nursing practice. (合理的医患沟通是建立良好护患关系、保证护理服务质量的前提和基础。本研究介绍医患沟通基本概念, 分析医患沟通在临床护理工作中的重要性, 研究临床护理中医患沟通的有效策略, 以期为临床开展医疗服务提供参考。)